Life cycle of Eimeria vejdovskyi Pakandl, 1988: electron microscopy study - Pakandl, M; Coudert, P (Parasitology research, 1999)
The endogenous development of the rabbit coccidium Eimeria vejdovskyi was studied in SPF rabbits using light and electron microscopy. All endogenous stages were seen in the ileal epithelium. There were two types of meronts in each of five asexual generations. Type A produced fat, polynucleate merozoites while type B meronts had slender uninucleate merozoites. First- second- and third-generation meronts were in the crypts. The first meronts were at the bottom of the crypts, very often in the Paneth cells. The meronts of the fourth generation were in the middle of the villi; the fifth-generation meronts were recorded in the middle and at the top of the villi. The prepatent period was 10 days.
Keywords: králíci; Coccidiosis; elektronová mikroskopie; Rabbits; Eimeria; ileum; Feces; parazitární nemoci střev; střevní sliznice; Animals; Intestinal Diseases, Parasitic; feces; Ileum; zvířata; kokcidióza; Intestinal Mucosa; Microscopy, Electron